Cerebrospinal fluid complement system biomarkers in demyelinating disease. (December 2020) - Zelek, Wioleta Milena; Fathalla, Dina; Morgan, Angharad; Touchard, Samuel; Loveless, Samantha; Tallantyre, Emma; Robertson, Neil P; Morgan, B Paul
Background: Multiple sclerosis (MS) can be difficult to differentiate from other demyelinating diseases, notably neuromyelitis optica spectrum disorder (NMOSD). We previously showed that NMOSD is distinguished from MS by plasma complement biomarkers. Objective: Here, we measure cerebrospinal fluid (CSF) complement proteins in MS, NMOSD and clinically isolated syndrome (CIS), a neurological episode that may presage MS, to test whether these distinguish NMOSD from MS and CIS. Materials and methods: CSF (53 MS, 17 CIS, 11 NMOSD, 35 controls) was obtained; complement proteins (C4, C3, C5, C9, C1, C1q, Factor B (FB)), regulators (Factor I (FI), Factor H (FH), FH-Related Proteins 1, 2 and 5 (FHR125), C1 Inhibitor (C1INH), Properdin) and activation products (terminal complement complex (TCC), iC3b) were quantified by ELISA and results expressed relative to CSF total protein (μg/mg). Results: Compared to control CSF, (1) levels of C4, C1INH and Properdin were elevated in MS; (2) TCC, iC3b, FI and FHR125 were increased in CIS; and (3) all complement biomarkers except TCC, FHR125, Properdin and C5 were higher in NMOSD CSF. A statistical model comprising six analytes (C3, C9, FB, C1q, FI, Properdin) plus age/gender optimally differentiated MS from NMOSD.